THE EFFECT OF MARKET VALUE ADDED, LEVERAGE, LIQUIDITY, COMPANY SIZE, AND SALES GROWTH ON LQ45 STOCK PRICES - Suci Arnita Sari; Zul Azmi; Muhammad Ahyaruddin (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to examine the effect of Market Value Added, Leverage, Liquidity, Firm Size, and Sales Growth on stock prices LQ45. The method used in this study is quantitative. The objects analyzed are companies listed on the LQ45 index for the 2019-2024 period, with sampling techniques using purposive sampling, resulting in 22 companies that meet the criteria. The method applied for data analysis is multiple linear regression analysis. The test outcomes reveal that Market Value Added positively and significantly impacts stock prices, Leverage negatively and significantly affects stock prices, whereas Liquidity and Firm Size do not have a significant impact on stock prices. Moreover, Sales Growth exerts a considerable negative impact on stock prices.